Perancangan Sistem Monitoring Data Pada Turbin Vortex Skala Laboratorium Berbasis Internet of Things (IoT) - Putra, Meiki Eru; Muslim, Muhammad (LPPM Universitas Dharma Andalas, 2024)
Forced vortex turbine is a turbine that utilizes water pressure to drive its turbine blades. Water is one of the natural resources that has not been utilized optimally, and is still rarely developed. The advantages of this vortex turbine that we make are very easy to operate, very minimal operational costs, can be monitored with a smartphone and also the LCD on the turbine, the ability to generate electricity, and can be used for practical mechatonic tools. course and energy conversion. There are many benefits of using a monitoring system as a measuring tool when checking data. The data to be monitored are water discharge, turbine rotation speed, generator rotation speed, vortex height, generated voltage, and power generated by the turbine. The C programming language is used to program the microcontroller that we use, because this programming language is classified as a programming language. programming that is not too complicated and the ESP32 microcontroller is used for control systems because it has a strong architecture with the input pins and output pins that we need fully available on this microcontroller, then features such as built-in WiFi, Bluetooth which are also built-in from the microcontroller and a large amount of memory. Then use the 4x20 LCD as a monitor where monitoring data from the turbine appears. Bluetooth which is also built-in from the microcontroller and a large amount of memory. Then use the 4x20 LCD as a monitor where monitoring data from the turbine appears. Bluetooth which is also built-in from the microcontroller and a large amount of memory. Then use the 4x20 LCD as a monitor where monitoring data from the turbine appears.